Gambling problems and associated harms in United Kingdom Royal Air Force personnel - Simon Dymond (Addictive Behaviors, 2022)
International evidence indicates that current and ex-military personnel may be at heightened vulnerability to problem gambling. The aim of the present study was to undertake the first survey of gambling experience and potential problems among serving United Kingdom Royal Air Force (RAF) personnel. Our objectives were to survey the frequency of gambling problems, types of gambling activities, examine mental health, alcohol use, and COVID-19-related associations with gambling, and identify potential risk factors among RAF personnel. A cross-sectional, online survey was distributed to all serving RAF personnel in January 2021 and the final dataset consisted of n=2,119 responses. The Problem Gambling Severity Index (PGSI) identified gambling severity, the Patient Health Questionnaire (PHQ-9) assessed depression, the Generalized Anxiety Disorder assessment (GAD-7) measured anxiety, and alcohol use was assessed with the Alcohol Use Disorders Identification Test (AUDIT). Questions relating to COVID-19 asked whether the pandemic had impacted one’s gambling, mental health, and alcohol use. Findings indicated that 12.5% of personnel reported gambling problems, which included 8.0% with PGSI scores indicating low-risk gambling (1-2), 2.9% moderate-risk gambling (3-4), and 1.6% with scores indicating problem gambling (≥8). Most personnel had no symptoms of depression or anxiety, and most experienced lower risk drinking levels. The likelihood of any gambling problem (PGSI≥1) in RAF personnel was associated with age (18-24 years old), male gender, and Non-Commissioned ranks. Most participants reported a deterioration in their mental health due to COVID-19 and increased risky gambling. These findings indicate that gambling problems and associated harms are significant concerns for serving RAF personnel.